Percutaneous radiofrequency ablation for medically inoperable patients with clinical stage I non‐small cell lung cancer. Issue 3 (22nd December 2014) - Liu, Baodong; Liu, Lei; Hu, Mu; Qian, Kun; Li, Yuanbo
Abstract: Background: A retrospective evaluation of percutaneous radiofrequency ablation (RFA) in medically inoperable patients with clinical stage I non‐small cell lung cancer (NSCLC). Methods: Between 2008 and 2014, 29 medically inoperable patients with clinical stage I NSCLC underwent percutaneous RFA. We evaluated the feasibility, safety, and effectiveness. Results: There were 18 men and 11 women with a median age of 78.0 years (range 56–85), mean 76.0 years. No procedure‐related deaths occurred in any of the 33 ablation procedures. The mean follow‐up was 25 months. The incidence of local tumor progression was 21.0% at 25 months of median time to progression after the initial RFA. The mean overall survival (OS) was 57 months (95% confidence interval (CI) 44–70 months). The mean cancer‐specific survival CSS was 63 months (95% CI 50–75 months). OS was 90.5% ± 6.4% at one year, 76.4% ± 10.7% at two, and 65.5% ± 13.6% at three years. CSS was 95.2% ± 4.6% at one, 86.6% ± 9.3% at two, and 74.2% ± 13.9% at three years in all patients. The survival for stage IA and IB cancers were 87.5% and 92.3% at one, 87.5% and 73.4% at two, and 87.5% and 58.7% at three years, respectively. Survival rates were not significantly different between the two groups ( P = 0.596), with mean survival times of 65 (95% CI: 51–79 months) and 55 months (95% CI: 38–71 months), respectively. Conclusion: Percutaneous RFA is a safe, feasible, and effective procedure in medically inoperable clinical stage I NSCLC patients.